Business networks along innovation life cycle. Issue 3 (1st May 2015) - Codini, Anna Paola
Abstract : Purpose: – This paper aims to investigate how the relationships among the different actors within the business networks affect the evolution of innovation along the different steps of technology life cycle. Design/methodology/approach: – The study is supported by a longitudinal case study referred to a mechanical company operating in the knitting machineries industry. A triangulation method integrating multiple data sources in a multiple method design was used to gather data. Findings: – The longitudinal study supports the idea that interactions among the actors within the business networks heavily influence the technology evolution. Research limitations/implications: – Although the longitudinal case study reported in this paper refers to a period of time of about 10 years, our findings refer only to a single case study in a specific sector and so they cannot be generalized. Practical implications: – This paper provides important guidelines on how to manage the relationships emerging within a business network to influence the new technologies development. Originality/value: – The paper contributes to business networks literature, filling the gaps about how the relationships among the actors involved in a network can evolve over time and influence the evolution of technology in itself.